Advances in management accounting - Burney, Laurie L.; Malina, Mary A. (Advances in management accounting, 2019)
This volume of Advances in Management Accountingexplores a variety of current issues through rigorous academic research. Topics include the link between CEO compensation and the 2008 financial crisis, the association between performance-based pay and employee honesty, and more.